Trends in Body Height, Body Weight, and Body Mass Index from 1979 to 1987: An Analysis of the Young Male Population from the Municipality of Cetinje - Bojan Masanovic; Srdja Martinovic; Gorica Zoric; Dragan Bacovic; Milena Mitrovic; Marina Vukotic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
This study aimed to consolidate body height, body weight, and body mass index data of the entire young male population from the Municipality of Cetinje in order to estimate trends from 1979 to 1987. The sample of respondents includes 2119 young males divided into nine groups: 183 respondents born in 1961, 361 respondents born in 1962, 300 respondents born in 1963, 162 respondents born in 1964, 155 respondents born in 1965, 258 respondents born in 1966, 218 respondents born in 1967, 234 respondents born in 1968, and 248 respondents born in 1969. The measurement sample includes body height, body weight, and body mass index calculated based on two previous measures. The descriptive statistics were expressed as a mean and standard deviation for each variable, while the analysis of nutrition status was done based on body mass index (underweight, normal weight, pre-obese, obese). The results showed that a secular trend in the observed study period is not visible regarding body height and body weight, while it is observable for the body mass index. Therefore, this study will contribute to complementing knowledge about changes in average body height values of young Montenegrins in the previous 120 years and in that way, more precisely monitor the emergence of a secular trend.